Caixa experimentoteca: uma proposta para o ensino de astronomia - Perez, Everton Piza [UNESP] (2015)
The sight of a starry sky on a clear night has fascinated humanity since prehistoric times. The man began to do sciense from the moment we wondered what were the stars and why they were there, drawing the appearance of the sky and trying to predict the celestial phenomena. From the time when Galileo pointed his telescope to the sky, began a close relationship between the evolution of astronomical instruments, technology, history and science. His act gave guided us to the Renaissance, culminating in the theory of universal gravitation Newton. Currently, many researches have been conducted within the theme of improving the teaching of science. However, the History of Science taught in Elementary and High School, and even on top, presentes problems as factual and conceptual errors. In order to provide better understanding of the phenomenon, this study intends to explore the use of a box of experiences through the use of educational material for Astronomy, called Experimentoteca case, related of astronomy that is taught in high school